Assessment Of Soil Suitability For Sertu Purification Based On Geological And Fiqh Views - Wan Ainaa Mardhiah Wan Zahari; Faizal Pakir; Aziman Madun; Nur Zainatul Nadra Zainol; Syaza Azhari (Universiti Sains Islam Malaysia, 2026)
The sertu purification process is an essential aspect of Islamic jurisprudence for removing najis mughallazah (severe impurities), such as contamination from dogs or pigs and their descendents. A key requirement in this process involves using water mixed with soil. However, ambiguity remains regarding the specific types and characteristics of soil that are suitable for use. This uncertainty raises practical and legal concerns, particularly as sertu is increasingly practiced in both personal and industrial contexts, and commercial soil products for sertu become more common. This study aims to evaluate the suitability of different soils for use in the sertu process based on their physical and chemical properties. Seven soil samples of varying origins and depths were analyzed using laboratory tests including particle size distribution, specific gravity, pH, organic content, X-ray diffraction (XRD), X-ray fluorescence (XRF), and cation exchange capacity (CEC). The results were assessed to determine whether differences in soil composition affect their performance and compliance with fiqh requirements. Findings indicate that while most soils share similar mineral compositions, variations in acidity, texture, and organic matter may influence their effectiveness. This study offers a scientific basis for selecting appropriate soil for sertu, supporting both technical validation and fiqh clarity in religious purification practices. The integration of geotechnical data with Islamic jurisprudence enhances the understanding and reliability of sertu, ensuring its correct implementation across various settings.